MANAJEMEN PEMBELAJARAN PKN DENGAN MODEL PROBLEM BASED INTRODUCTION (PBI) BAGI SISWA SMK - Varianita Varianita Varianita (UNIVERSITAS BENGKULU, 2016)
The purpose of this study is to know learning outcomes with citizenship learning management through model of problem-based learning introduction (PBI). This classroom action research conducted in SMKN 2 Kota Bengkulu. Subjects of the study were students of class XI TP with 17 students. Data collection techniques using test, observation and documentation. Analysis of the data used descriptive analysis. Data analysis results in terms of learning assessment resultsand student activity changes step by step If the comparison between the state of the initial conditions, the first cycle and the second cycle can be seen that when the initial conditions average grade of 4.83, while the average value of the class existing second cycle increased to 6.67. The average increase in the second cycle to 7.66. Thus the study of this class action is successful so the researchers recommend citizenship learning management through problem-based learning introduction.Keywords : learning outcome, problem based introduction, management, citizenship